Obesity : the Venus of Willendorf - Eckdahl, Todd T. (Human diseases and conditions collection., 2019)
Obesity is a global health problem that has reached epidemic levels. The worldwide prevalence of adult obesity is 13 percent of adults and 7 percent of children. This book describes how obesity results from an imbalance between the intake of food energy and the expenditure of energy from physical activity and increases the risk of serious health problems including heart disease, stroke, osteoarthritis, and several types of cancer. The author explains how body mass index (BMI) can be used to screen for obesity, but that its diagnosis depends on the clinical laboratory measurement of total body fat content and distribution. The book describes rare forms of obesity caused by a single gene or a genetic syndrome, and common obesity, a complex disease caused by multiple genetic and environmental risk factors. The book presents examples of obesity susceptibility genes and describes obesity genetic testing. It explains that obesity usually can be treated with dietary changes, increased physical activity, and behavioral modification, but that people with extreme obesity or those who have serious health complications require pharmaceutical or surgical interventions. The book describes promising prospects for the treatment of obesity involving new pharmaceuticals, stem cell therapy, gene therapy, and fecal microbiota transplants.